Investigating Non-Medical Ethics Committee Monitoring Approaches and its Effectiveness - Schoeman, Shaun (University of the Witwatersrand, Johannesburg, 2024)
Ethics committee monitoring aims to ensure that research participants are protected throughout the research process and to ensure that research is conducted ethically. This study investigates monitoring approaches used by non-medical ethics committees within South Africa in a climate of limited resources and the relationship with the governing guidelines. The study further investigates the current monitoring approaches that are used and how effective these are in relation to participant protection. The study found that the current monitoring approaches used by non-medical ethics committees are passive as opposed to active. Non-medical ethics committees face challenges such as limited resources, funding, training, and ineffective guidelines that hinder their ability to monitor more effectively. The governing monitoring guidelines for registered ethics committees are premised on medical ethics, which is not fit the purpose of non-medical ethics committee monitoring. The study proposes adjustments to these governing guidelines, taking limited resources and non-medical nuances into consideration. The study further suggests that passive monitoring be redefined to include more effective methods than just annual progress reporting. These methods include participant meetings or citizen monitoring to ensure that participants are protected, and that research is conducted ethically.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Monitoring; Non-Medical Ethics Committees; Guidelines; Passive Monitoring; Active Monitoring; SDG-3: Good health and well-being